Observational study: 27 years of severe malaria surveillance in Kilifi, Kenya - Njuguna, P; Maitland, K; Nyaguara, A; Lowe, B; Atkinson, S; Snow, RW; Marsh, K; Berkley, JA; Newton, CRJ; Bejon, P (BioMed Central, 2019)
Background: Many parts of Africa have witnessed reductions in Plasmodium falciparum transmission over the last 15 years. Since immunity to malaria is acquired more rapidly at higher transmission, the slower acquisition of immunity at lower transmission may partially offset the benefits of reductions in transmission. We examined the clinical spectrum of disease and predictors of mortality after sustained changes in transmission intensity, using data collected from 1989 to 2016. Methods: We conducted a temporal observational analysis of 18,000 children, aged 14 days to 14 years old, who were admitted to Kilifi County Hospital, Kenya, from 1989 to 2016 with malaria. We describe the trends over time of the clinical and laboratory criteria for severe malaria and associated risk of mortality. Results: During the time periods 1989–2003, 2004–2008, and 2009–2016, Kilifi County Hospital admitted averages of 657, 310, and 174 cases of severe malaria per year including averages of 48, 14, and 12 malaria-associated deaths per year, respectively. The median ages in years of children admitted with cerebral malaria, severe anaemia, and malaria-associated mortality were 3.0 (95% confidence interval (CI) 2.2–3.9), 1.1 (95% CI 0.9–1.4), and 1.1 (95% CI 0.3– 2.2) in the year 1989, rising to 4.9 (95% CI 3.9–5.9), 3.8 (95% CI 2.5–7.1), and 5 (95% CI 3.3–6.3) in the year 2016. The ratio of children with cerebral malaria to severe anaemia rose from 1:2 before 2004 to 3:2 after 2009. Hyperparasitaemia was a risk factor for death after 2009 but not in earlier time periods. Conclusion: Despite the evidence of slower acquisition of immunity, continued reductions in the numbers of cases of severe malaria resulted in lower overall mortality. Our temporal data are limited to a single site, albeit potentially applicable to a secular trend present in many parts of Africa.